Efforts of Different Regimes in Kenya Toward National Cohesion and Integration, 1963-2022 - Benson Nyamweno (African Journal of Political Science)
Kenya like many states in the African continent is a multi-ethnic nation. Since its independence in 1963, Kenya has had challenges in putting together its communities. Conflict always arises as a result of the unequal distribution of resources among communities. This article will strive to unravel the efforts of different regimes in Kenya since its independence in achieving national cohesion and integration. The article argues for a rethinking of socio-economic policies through political goodwill and instilling national ethos, otherwise, the initiatives for national cohesion and integration will be in vain, stillborn, and frustrated across the nation. To adequately answer the above question, the researcher will be guided by this sole objective which is to examine the efforts of different regimes in Kenya toward achieving national cohesion and integration. The assumptions of the study will be, ethnic conflict is influenced by the context, typology of actors, and nature of the divergent interests sought for. The study is expected to offer a unique opportunity for policymakers to understand the political context and varied interests of various political players to not only predict the outcome but also determine the agenda-setting for national cohesion and integration in Kenya. The article adopted a qualitative approach by going through available literature on the subject matter to reach a logical conclusion. The author concludes by offering policy recommendations necessary for achieving national cohesion and integration in Kenya.